2012
DOI: 10.4132/koreanjpathol.2012.46.4.341
|View full text |Cite
|
Sign up to set email alerts
|

Loss of E-cadherin and Acquisition of Vimentin in Epithelial-Mesenchymal Transition are Noble Indicators of Uterine Cervix Cancer Progression

Abstract: BackgroundEpithelial-mesenchymal transition (EMT) has been known to play a key role in the stromal invasion of carcinoma in situ (CIS) lesion. Loss of E-cadherin and acquisition of vimentin are two critical steps in EMT, that are induced by Snail-1 upregulation associated with overexpression of epidermal growth factor receptor (EGFR). However, roles of EMT-related proteins in human cervical tissues have not been fully elucidated. In this study, we investigated the immunoexpressions of EMT-related proteins in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 18 publications
9
56
4
1
Order By: Relevance
“…EGFR has been found to be overexpressed in cervical cancer 23 and to be an important inducer of EMT. 24,25 EGFR activation up-regulates Snail expression to promote EMT and progression of cervical cancer. 26 Another important tyrosine kinase receptor is EphB2, the activation of which is recently demonstrated to promote EMT through Ras signal pathway in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR has been found to be overexpressed in cervical cancer 23 and to be an important inducer of EMT. 24,25 EGFR activation up-regulates Snail expression to promote EMT and progression of cervical cancer. 26 Another important tyrosine kinase receptor is EphB2, the activation of which is recently demonstrated to promote EMT through Ras signal pathway in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cells undergoing EMT lose epithelial markers such as E-cadherin and gain mesenchymal markers such as vimentin and fibronectin. The constitutively-activated NF-ÎșB pathway in tumors has been reported to be involved in the EMT switch through the regulation of target genes, such as Snail family members, that result in the repression of E-cadherin (Myong, 2012). Our findings with the dysregulated NF-ÎșB/Snail/YY1/RKIP loop in cancer suggested that each member of this loop would be also involved in the regulation of EMT, particularly since YY1 regulates Snail and Snail is directly involved in EMT (Bonavida & Baritaki, 2011a, 2011b.…”
Section: Regulation Of Epithelial-mesenchymal Transition By Yin Yangmentioning
confidence: 99%
“…In particular, HPV E6 oncoprotein expression induces characteristic changes in EMT 32. Myong and collaborators showed that the loss of E‐cadherin and gain of vimentin are found within more aggressive cervical‐derived invasive lesions but not within preneoplastic alterations 33. Our results suggest that the presence of EMT markers negatively affected women with locally advanced CC.…”
Section: Discussionmentioning
confidence: 56%